Can sports cartoon watching in childhood promote adult physical activity and mental health? A pathway analysis in Chinese adults. Issue 5 (May 2022) - Zhang, Xing; Browning, Matthew H.E.M.; Luo, Yong; Li, Hansen
Abstract: Physical activity is essential to maintain physical and mental health. Unfortunately, insufficient physical activity has become a common phenomenon worldwide in the past decade, and the absence of interest in physical activity is assumed a reason. Therefore, strategies for fostering interests and promoting public engagement are in need. We conducted a questionnaire survey during September 2021 that involved 1202 adults to capture data on sports and relevant cartoon watching experiences during childhood; Intensity and frequency of physical activity, depression (PHQ-9), and anxiety (GAD-7) during adulthood. Structural equation modeling was employed to examine pathways between watching sports cartoon in childhood and physical activity and mental health in adulthood. The results suggest that childhood sports cartoon watching may have indirect and positive impacts on adult physical activity and, in turn, on mental health. Childhood sports experience is a critical mediator role linking childhood sports cartoon watching, adult physical activity, and adult mental health. In conclusion, watching sports cartoon may help cultivate sports interests and promote children's participation in sports, and the sports experiences may be a continuous and beneficial factor that connects childhood and adulthood. These findings indicate a framework to understand the durative positive impact of cartoons and maybe other children's film and television works. Abstract : Sports cartoon; Child; Childhood; Mental health; Physical activity; Sports.